2016
DOI: 10.4269/ajtmh.15-0197
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Determinants of the Distribution of Chagas Disease Vector Triatoma dimidiata in Colombia

Abstract: Abstract. Triatoma dimidiata (Hemiptera: Reduviidae) is a secondary vector of Trypanosoma cruzi in Colombia and represents an important epidemiological risk mainly in the central and oriental regions of the country where it occupies sylvatic, peridomestic, and intradomestic ecotopes, and because of this complex distribution, its distribution and abundance could be conditioned by environmental factors. In this work, we explored the relationship between T. dimidiata distribution and environmental factors in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 42 publications
0
19
0
3
Order By: Relevance
“…It has been documented that at the global scale (in the Americas), its distribution is influenced by the Bio03 and Bio06 (de la Vega & Schilman, 2018). Still, at a regional scale, the species presents climatic similarities with the Phyllosoma complex, because its distribution is also mainly determined by the Bio04 in Colombia (Parra-Henao et al, 2016) and México (Carmona-Castro et al, 2018) or is strongly associated with temperature and precipitation (Yucatan Peninsula, Mexico in Dumonteil et al, 2002;Dumonteil & Gourbière, 2004). Interestingly, the similarity or niche conservatism among the Phyllosoma complex and T. dimidiata lineages has never been evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…It has been documented that at the global scale (in the Americas), its distribution is influenced by the Bio03 and Bio06 (de la Vega & Schilman, 2018). Still, at a regional scale, the species presents climatic similarities with the Phyllosoma complex, because its distribution is also mainly determined by the Bio04 in Colombia (Parra-Henao et al, 2016) and México (Carmona-Castro et al, 2018) or is strongly associated with temperature and precipitation (Yucatan Peninsula, Mexico in Dumonteil et al, 2002;Dumonteil & Gourbière, 2004). Interestingly, the similarity or niche conservatism among the Phyllosoma complex and T. dimidiata lineages has never been evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…infestans and R. prolixus), bringing insights into the distribution of the triatomine group as a whole. Specific studies were carried out for Venezuela [19,53], Argentina [53], Colombia [21,23] and Ecuador [54]. For Brazil, in particular, [10] analyzed the distribution of eight species in the center-west region and [55] analyzed the distribution of the species complex T. brasiliensis, which occurs mainly in the Brazilian northeast.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies has shown that triatomines can have different levels of adaptation to anthropogenic environments [13,22]. They are organisms that can move around actively looking for microenvironments that meet their ecological demands and, thus, the species can infest best suited household and peridomestic areas [22,23]. These different levels of successful colonization of anthropic environments can be interpreted as different levels of ecological interaction between different species of triatomine vectors and the human species.…”
Section: Introductionmentioning
confidence: 99%
“…La fauna de triatominos ha sido ampliamente estudiada debido a su importancia epidemiológica (Salazar y Calle, 2003;Guhl et al, 2007); en Colombia varias investigaciones han tratado el tema de la caracterización ecoepidemiológica de algunas especies de triatominos asociados a palmas (Salazar y Calle, 2003;Guhl et al, 2007;Parra-Henao et al, 2016). Los resultados presentes, con respecto a triatominos en la palma de vino, se relacionan con las publicaciones acerca del tema; las dos especies encontradas en esta investigación también han sido encon-tradas en A. butyracea y otras palmas en dife-rentes regiones del país.…”
Section: Discussionunclassified